2000
DOI: 10.1038/emm.2000.37
|View full text |Cite
|
Sign up to set email alerts
|

Activation of JNK and p38 in rat hippocampus after kainic acid induced seizure

Abstract: Kainic acid, an analogue of glutamate, causes limbic seizures and induces cell death in the rat brain. We examined the activation of MAPK family kinases; ERKs, JNKs and p38 kinase in rat hippocampus after KA treatment. Activation of all three kinases were observed at 30 min after the treatment, but, in contrary to ERK phosphorylation, which lasted up to 3 h, the phosphorylation of JNK and p38 returned to the basal level by 2 h. The phosphorylation of upstream kinases for the MAPK family was distinct. The phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 22 publications
6
43
1
Order By: Relevance
“…Activation of the MAP kinase (MAPK) family following seizure activity was previously described (25,39). Our model of nicotine-induced seizures detected four differentially overexpressed genes, Fos, Nr4a1, Dusp1, and Nfkbia, involved in the MAPK signaling pathway.…”
Section: Discussionsupporting
confidence: 57%
“…Activation of the MAP kinase (MAPK) family following seizure activity was previously described (25,39). Our model of nicotine-induced seizures detected four differentially overexpressed genes, Fos, Nr4a1, Dusp1, and Nfkbia, involved in the MAPK signaling pathway.…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore ERK activation may afford protection against c-Jun N-terminal kinase (JNK)-mediated cell death (Xia et al, 1995). Interestingly, JNK is stimulated by seizure activity in the hippocampus (Jeon et al, 2000), and thus repressed ERK activity may increase the vulnerability of hilar interneurons to excitotoxic cell death via JNK-dependent signaling. In this context, it is interesting to note that somatostatinergic hilar interneurons are highly vulnerable to a number of excitatory insults, including ischemia and trauma, as well as SE (Lowenstein et al, 1992;Matsuyama et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…injection. Several studies reported that the p-ERK was increased by systemic administration of KA in the rat hippocampus (Mielke et al, 1999;Jeon et al, 2000). Recent studies showed that seizures induced the sprouting of mossy fibers in the rat hippocampus CA3 region (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…KA, administered i.c.v., induced the lesion of CA3 pyramidal neurons in mice (Ferraguti et al, 2001;Lee et al, 2002;Lee et al, 2003). The phosphorylated extracellular signal-regulated kinase (p-ERK) is increased by systemic administration of KA in the rat hippocampus (Mielke et al, 1999;Jeon et al, 2000). Seizures induce the sprouting of mossy fibers in the CA3 region of rat hippocampus (Ben-Ari and Cossart, 2000).…”
Section: Introductionmentioning
confidence: 99%